PENGARUH MOTIVASI BELAJAR, INTEGRITAS MAHASISWA, DAN PENYALAHGUNAAN TEKNOLOGI INFORMASI TERHADAP PERILAKU KECURANGAN AKADEMIK - Nabilah Sarah Hafizhah; Fajar Syaiful Akbar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research has been established to examine the influence of learning motivation, student integrity and the misusage of information technology towards academic fraud. The sampling method that has been applied for conducting this research is called probability sampling using the random sampling method as a probability sampling technique. In carrying out this research, samples have been taken among 171 students who graduated in accountancy with a bachelor's degree from UPN